Madre-figlia: un binomio complesso - Serkowska, Hanna (Studia Romanica Posnaniensia, 2018)
The article examines some decisive transformations that took place in the representation of the motherdaughter relationship, reflected in texts written by Italian women writers between the early 1900s and the early 2000s. Although updated, both motherhood and mother-daughter relationship appear closely linked and anchored to problems that imprison women in various predicaments. The corpus here under analysis focuses on unusual literary genealogies.